Determinants of culinary Students’ Entrepreneurial Intentions: The role of social media use within dual-theory frameworks - Xinling Zhong (PLoS ONE, 2026)
China’s national “mass entrepreneurship and innovation” strategy has sparked growing attention toward cultivating entrepreneurial competencies among university students. As a vital resource and interactive platform, social media profoundly shapes the entire entrepreneurial process. However, existing research lacks a systematic examination of the mechanisms through which social media influences entrepreneurial intentions (EI)—particularly among culinary students. Grounded in Social Cognitive Theory (SCT) and the Theory of Planned Behavior (TPB), this study examines the influence of social media use (SMU) on EI among culinary students. Using a snowball sampling method, the researchers surveyed 499 students, collecting self-reported responses across six constructs: SUM, subjective norms (SN), entrepreneurial self-efficacy (ESE), entrepreneurial attitude (EA), perceived behavioral control (PBC), and EI. A two-stage analytical approach combining Structural Equation Modeling and Artificial Neural Networks was employed to uncover the constructs’ complex, nonlinear, and non-compensatory relationships. The results revealed that SMU does not directly influence EI; instead, it exerts a positive indirect effect through the mediating roles of PBC, ESE, and EA. Moreover, the normalized importance derived from the multilayer perceptron indicated that EA (100%) is the most significant predictor of entrepreneurial intention among culinary arts students. This study offers theoretical and practical insights into how social media can be leveraged to foster entrepreneurship among students in the culinary field.